ANALYSIS OF THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND LEARNING MOTIVATION ON STUDENT ACADEMIC ACHIEVEMENT - Oktariani (Adisam Publisher, 2026)
This research aims to analyze the influence of emotional intelligence and learning motivation on student academic achievement through a literature review. The method used is a literature study by examining various previous research relevant to this topic. The findings of the literature review show that emotional intelligence has a significant relationship with students' learning motivation and academic achievement. Students who have high emotional intelligence tend to be better able to manage stress, have good adaptability, and are able to regulate their emotions effectively, which in turn increases their learning motivation. High learning motivation is consistently associated with better academic achievement. This study also highlights the importance of implementing social-emotional learning programs in higher education curricula to improve students' emotional skills. It is hoped that the integration of emotional intelligence in teaching methods can create a more supportive and challenging learning environment. It is hoped that the results of this research can contribute to improving educational strategies that are more comprehensive by considering students' emotional and motivational aspects. This research concludes that developing emotional intelligence and increasing learning motivation are effective strategies for improving student academic achievement. Therefore, higher education institutions are advised to adopt a holistic approach in the teaching and academic guidance process, in order to create students who are not only academically competent, but also have good emotional well-being.